Endoscopic ultrasound-guided gallbladder drainage versus percutaneous cholecystostomy for high risk surgical patients with acute cholecystitis: a systematic review and meta-analysis - Luk, Sally Wai-Yin; Irani, Shayan; Krishnamoorthi, Rajesh; Wong Lau, James Yun; Wai Ng, Enders Kwok; Teoh, Anthony Yuen-Bum (Endoscopy, 2019)
Background Recent evidence suggests that endoscopic ultrasound-guided gallbladder drainage (EUS-GBD) is an effective and safe alternative to percutaneous drainage (PT-GBD). We conducted a systematic review and meta-analysis to compare these two procedures in high risk surgical patients with acute cholecystitis. Methods A comprehensive electronic literature search was conducted for all articles published up to October 2017 to identify comparative studies between EUS-GBD and PT-GBD. A meta-analysis was performed on outcomes including technical success, clinical success, post-procedure adverse events, length of hospital stay, unplanned hospital readmission, need for reintervention, recurrent cholecystitis, and disease- or treatment-related mortality for these two procedures.Results Five comparative studies (206 patients in the EUS-GBD group vs. 289 patients in the PT-GBD group), were included in the final analysis. There were no statistically significant differences in technical success (odds ratio [OR] 0.43, 95 % confidence interval [CI] 0.12 to 1.58; P  = 0.21; I2 = 0 %) and clinical success (OR 1.07, 95 %CI 0.36 to 3.16; P  = 0.90; I2 = 44 %) between the two procedures. EUS-GBD had fewer adverse events than PT-GBD (OR 0.43, 95 %CI 0.18 to 1.00; P  = 0.05; I2 = 66 %). Moreover, patients undergoing EUS-GBD had shorter hospital stays, with pooled standard mean difference of – 2.53 (95 %CI – 4.28 to – 0.78; P = 0.005; I2 = 98 %), and required significantly fewer reinterventions (OR 0.16, 95 %CI 0.04 to 0.042; P <  0.001; I2 = 32 %) resulting in significantly fewer unplanned readmissions (OR 0.16, 95 %CI 0.05 to 0.53; P  = 0.003; I2 = 79 %). Conclusions EUS-GBD was associated with lower rates of post-procedure adverse events, shorter hospital stays, and fewer reinterventions and readmissions compared with PT-GBD in patients with acute cholecystitis who were unfit for surgery.